990Seaweed intake and risk of cardiovascular disease: the Japan Public Health Center–based Prospective (JPHC) Study. (2nd September 2021) - Murai, Utako; Yamagishi, Kazumasa; Sata, Mizuki; Kokubo, Yoshihiro; Saito, Isao; Yatsuya, Hiroshi; Ishihara, Junko; Inoue, Manami; Sawada, Norie; Iso, Hiroyasu; Tsugane, Shoichiro
Abstract: Background: The minerals, vitamins, soluble dietary fibers, and flavonoids of seaweed are protective for preventing cardiovascular diseases. However, the association between seaweed intake and risk of cardiovascular disease has not been established. We examined the dietary intake of seaweed and its impact upon stroke and ischemic heart disease (IHD) risk among a Japanese study population. Methods: We surveyed 40, 707 men and 45, 406 women from 2 large cohorts (age range: 40–69 y). Seaweed intake in the study subjects was estimated from the food frequency questionnaire at baseline (1990–1994). Stroke and IHD events were identified until the end of 2009 (Cohort I) or 2012 (Cohort II). The hazard ratios (HRs) (95% confidence intervals [CIs]) for incident cardiovascular disease (CVD) and its subtype were estimated using Cox proportional hazard models after stratification by area and adjustment for cardiovascular disease risk and dietary factors by sex. Results: During 1, 493, 232 person-years of follow-up, 4, 777 strokes and 1, 204 IHD cases were identified. Among men, significant multivariable HRs (95% CIs) for almost daily consumption were seen in IHD (0.76 [0.58-0.99]; P-trend=0.04) compared to almost no seaweed consumption. Among women, such inverse associations were observed in incident IHD (0.56 [0.36-0.85]; P-trend=0.006). No significant associations were observed between seaweed intake and risk of stroke nor stroke subtypes among either men or women. Conclusions: Seaweed intake has been shown to contribute to the prevention of IHD in a large Japanese cohort. Key messages: Seaweed intake could be beneficial for prevention of IHD.